2020
DOI: 10.2147/pgpm.s260209
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association of <em>MDM4</em> Gene rs4245739 Polymorphism with the Risk and Clinical Characteristics of Colorectal Cancer in a Chinese Han Population</p>

Abstract: Background: Studies show that MDM4 may play a pivotal role in colorectal cancer (CRC). Recently, a host of studies suggest that MDM4 gene rs4245739 polymorphism may modify the risk of different cancers. Methods: In this study, we were interested whether MDM4 gene rs4245739 polymorphism correlated with the risk and clinical characteristics of CRC. Logistic regression was adopted to estimate the association of rs4245739 polymorphism and CRC risk. Results: We enrolled 444 CRC patients and 530 controls and found M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…For polymorphisms of MDM4 gene (rs1380576, rs1563828, rs10900598, rs11801299, and rs4245739), a total of 15 articles (including 29 case–control studies) with 21,365 cases and 29,280 controls met the inclusion criteria. 9-23 A total of 14 studies were performed in Asians, 11 studies were performed in Caucasians, and four studies in Iranian-Azeri. Controls of 19 studies were population-based controls and 10 studies were hospital-based controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For polymorphisms of MDM4 gene (rs1380576, rs1563828, rs10900598, rs11801299, and rs4245739), a total of 15 articles (including 29 case–control studies) with 21,365 cases and 29,280 controls met the inclusion criteria. 9-23 A total of 14 studies were performed in Asians, 11 studies were performed in Caucasians, and four studies in Iranian-Azeri. Controls of 19 studies were population-based controls and 10 studies were hospital-based controls.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled results based on 17 included studies (including 13,876 cases and 20,212 controls) indicated that rs4245739 was significantly related to a reduced risk of cancer in allelic contrast (B vs. A: OR = 0.83, 95% CI = 0.75-0.92, P = 0.000) and dominant model (AB + BB vs. AA: OR = 0.81, 95% CI = 0.71-0.91, P = 0.001). [9][10][11][17][18][19][20][21][22][23] Then, in the stratification analysis by cancer type, we observed that rs4245739 polymorphism was significantly related to a decreased risk of breast cancer in a recessive model (BB vs. AA + AB: OR = 0.75, 95% CI = 0.59-0.95, P =0.019, Figure 2). In addition, in the stratification analysis by ethnicity, we observed that rs4245739 polymorphism was significantly related to a decreased cancer risk for Asians in allelic contrast (B vs. A: OR = 0.56, 95% CI = 0.48-0.66, P = 0.000, Figure 3), dominant model (BB + AB vs. AA: OR = 0.54, 95% CI = 0.46-0.64, P = 0.000) and recessive model (BB vs. AA + AB: OR = 0.56, 95% CI = 0.32-0.98, P = 0.041).…”
Section: Quantitative Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“… 8 , 9 , 10 , 11 Single nucleotide polymorphisms (SNPs), the most common and effective variant type, are significantly associated with cancer susceptibility. 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Single nucleotide polymorphisms (SNPs), the most common and effective variant type, are significantly associated with cancer susceptibility. [12][13][14] NF-κB, short for nuclear factor kappa B, is a pluripotent and critical dimer transcription factor. NF-κB orchestrates multiple physiological and pathological processes, particularly in cell survival, differentiation, inflammation and carcinogenesis.…”
mentioning
confidence: 99%